DEVELOPMENT OF WEST KALIMANTAN VOLLEYBALL COMPETITION SYSTEM THROUGH WEB-BASED APPLICATIONS - Syaparudin, Syaparudin; Rahmat, Ade; Suhairi, Muhammad (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
The purpose of this research is to develop a web-based volleyball match system made in accordance with the concept of the PP PBVSI match system, this system is designed to make it easier for West Kalimantan PBVSI Pengprov in making match systems automatically and online. This study uses the Research and Development method adopted from the ADDIE development (Analysis, Design, Development, Implementation, Evaluation). The research subjects were 85 participants from the official volleyball team at the 2023 West Kalimantan Regional Police Chief Championship 2023. Involved two material validation experts consisting of academics and practitioners, one media expert from a lecturer in the Computer Science Technology study program. Data collection in this study used open and closed questionnaires, which contained a suggestion column. Questionnaires and questionnaires were given to validators with the aim of obtaining data about the feasibility level of web-based competition system applications in the form of numbers as a basis for product revisions. Data analysis techniques were carried out qualitatively and quantitatively. Data quality is obtained from expert validation activities in the form of suggestions, responses, and input related to the product being developed. Quantitative data in the form of assessments collected from the point of view or product trial questionnaires during the trial activities were analyzed using descriptive statistics. The results of the study can be concluded that the web-based match system can be used in implementing actual volleyball competitions. This application also makes it easier for the West Kalimantan PBVSI Pengprov, especially in the field of competition, where time is more efficient in determining the Pool champion and Runer-Up Pool in each group..